Hypoxic culture of umbilical cord mesenchymal stem cell-derived sEVs prompts peripheral nerve injury repair - Zhu, Ziying; Zhang, Yujun; Huang, Zhihua; Hao, Haojie; Yan, Muyang (Frontiers in Cellular Neuroscience, 2023)
Repair and regeneration of the peripheral nerve are important for the treatment of peripheral nerve injury (PNI) caused by mechanical tears, external compression injuries and traction injuries. Pharmacological treatment can promote the proliferation of fibroblasts and Schwann cells (SCs), which longitudinally fill the endoneurial canal and form Bungner's band, helping the repair of peripheral nerves. Therefore, the development of new drugs for the treatment of PNI has become a top priority in recent years. Here, we report that small extracellular vesicles (sEVs)produced from umbilical cord mesenchymal stem cells (MSC-sEVs) cultured under hypoxia promote repair and regeneration of the peripheral nerve in PNI and may be a new therapeutic drug candidate. The results showed that the amount of secreted sEVs was significantly increased in UC-MSCs compared with control cells after 48 h of culture at 3% oxygen partial pressure in a serum-free culture system. The identified MSC-sEVs could be taken up by SCs in vitro, promoting the growth and migration of SCs and preventing apoptosis-induced damage to some extent. In a spared nerve injury (SNI) mouse model, MSC-sEVs accelerated the recruitment of SCs at the site of PNI and promoted peripheral nerve repair and regeneration. Notably, repair and regeneration in the SNI mouse model were dose-dependently enhanced by treatment with hypoxic cultured UC-MSC-derived sEVs. Therefore, we conclude that hypoxic cultured UC-MSC derived sEVs may be a promising candidate drug for repair and regeneration in PNI.